Effect of Levetiracetam Use Duration on Overall Survival of Isocitrate Dehydrogenase Wild-Type Glioblastoma in Adults. Issue 5 (September 2022) - King-Stephens, David
Effect of Levetiracetam Use Duration on Overall Survival of Isocitrate Dehydrogenase Wild-Type Glioblastoma in Adults: An Observational Study Pallud J, Huberfeld G, Dezamis E, et al. Neurology . 2022;98(2):e125-e140. doi:10.1212/WNL.0000000000013005 . Background and Objectives: The association between levetiracetam and survival with isocitrate dehydrogenase (IDH) wild type glioblastomas is controversial. We investigated whether the duration of levetiracetam use during the standard chemoradiation protocol affects overall survival (OS) of patients with IDH wild-type glioblastoma. Methods: In this observational single-institution cohort study (2010-2018), inclusion criteria were (1) age=18 years; (2) newly diagnosed supratentorial tumor; (3) histomolecular diagnosis of IDH wild-type glioblastoma; and (4) standard chemoradiation protocol. To assess the survival benefit of levetiracetam use during the standard chemoradiation protocol (whole duration, part time, and never subgroups), a Cox proportional hazard model was constructed. We performed a case-matched analysis (1:1) between patients with levetiracetam use during the whole du ration of the standard chemoradiation protocol and patients with levetiracetam use part time or never according to the following criteria: sex, age, epileptic seizures at diagnosis, Radiation Therapy Oncology Group recursive partitioning analysis (RTOG-RPA) class, tumor location, preoperative volume, extent of resection, and O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation status. Patients with unavailable O6-methylguanine-DNA methyltransferase promoter methylation status (48.5%) were excluded. Results: A total of 460 patients were included. The median OS was longer in the 116 patients with levetiracetam use during the whole duration of the standard chemoradiation protocol (21.0 months; 95% confidence interval [CI] 17.2-24.0) than in the 126 patients with part-time levetiracetam use (16.8 months; 95% CI 12.4-19.0) and in the 218 patients who never received levetiracetam (16.0 months; 95% CI 15.5-19.4; P = .027). Levetiracetam use during the whole duration of the standard chemoradiation protocol (adjusted hazard ratio [aHR] .69; 95% CI .52-.93; P = .014), MGMT promoter methylation (aHR .53; 95% CI .39-.71; P < .001), and gross total tumor resection (aHR .57; 95% CI .44-.74; P < .001) were independent predictors of longer OS. After case matching (n = 54 per group), a longer OS was found for levetiracetam use during the whole duration of the standard chemoradiation protocol (hazard ratio .63; 95% CI .42-.94; P = .023). Discussion: Levetiracetam use during the whole standard chemoradiation protocol possibly improves OS of patients with IDH wild-type glioblastoma. It should be considered in the antitumor strategy of future multicentric trials. Classification of evidence: This study provides Class III evidence that in individuals with IDH wild-type glioblastoma, levetiracetam use throughout the duration of standard chemotherapy is associated with longer median OS.